Instituţia Ombudsmanului: Justiţie Alternativă? (The Ombudsman Institution: Alternative Justice?) - Cristian RADU (Transylvanian Review of Administrative Sciences, 2012)
Dacian-Cosmin DRAGOŞ and Bogdana NEAMŢU (editors), Instituţia Ombudsmanului: Justiţie Alternativă? (The Ombudsman Institution: Alternative Justice?), Bucharest, C.H. Beck, 2011